Synthesis and characterization of CuO-MgO-ZnO and CuO-Co3O4-CeO2 - Dias, Leonardo Francisco Gonçalves; Pimentel, Gabriel Junior Cavalcante [UNESP]; Rheinheimer, João Pedro Costa [UNESP]; Gomes, Orisson Ponce [UNESP]; de Almeida, Bianca Gottardo [UNESP]; Volanti, Diogo Paschoalini [UNESP]; de Almeida, Margarete Teresa Gottardo; Lisboa-Filho, Paulo Noronha [UNESP] (Springer Nature, 2023)
The synthesis of trioxides offers unique properties for different applications due to the combination of multiple oxides; however, few studies have reported on the properties of these materials, especially in terms of their ability to create reactive oxygen species, which are helpful for antibacterial and antifungal activity. This study aimed to evaluate the surface properties of CuO-MgO-ZnO and CuO-Co3O4-CeO2 trioxides synthesized via precipitation assisted by an ultrasonic bath or sonication. The structural analysis indicated the formation of micrometric particles consisting of individual phases of each oxide, with no apparent influence of the preparation method on their morphology. UV–Vis spectroscopy revealed that CuO-MgO-ZnO particles have a band gap near 5.5 eV, while CuO-Co3O4-CeO2 has a single value at 4.2 eV. Zeta potential measurements indicated changes in the materials' outermost layer composition due to the synthesis method. Additionally, biological assays showed that the materials could completely inhibit the growth of Candida species and Staphylococcus aureus but not Klebsiella pneumoniae. These results suggest that the materials may be suitable for self-cleaning surfaces and medical device coatings.
Keywords: Antibacterial; Antifungal; Precipitation method; Surface characterization; Trioxide